ANALISIS KEPUASAN TAMU DI LOTUS LOUNGE WYNDHAM OPI HOTEL PALEMBANG - Ahmad Alhaq; Ahmad Khudri; Margriet Puspa Dewi (STKIP Subang, 2026)
This study aims to analyze guest satisfaction at the Lotus Lounge, Hotel Whyndam OPI, Palembang. Furthermore, this study aims to expand knowledge and provide scientific references in the field of hotel management, particularly regarding the analysis of guest satisfaction in the hotel industry. This study also contributes to the development of theories on guest satisfaction in hotel and restaurant services. The results of this study can serve as a basis for further research addressing guest satisfaction in the hotel and restaurant sector. The method used in this study is qualitative with a quantitative approach to the research object. The data used in this study are primary data collected through interviews, observations, and direct attendance with hotel management and consumers. Secondary data obtained from primary sources, namely consumers, in the form of questionnaires, and literature such as books, journals, and previous research related to the discussion. The results obtained from this study indicate that efforts have been made, but their implementation is still not optimal.